Réponses

  • Omnes
  • Modérateur confirmé
2014-03-09T22:21:04+01:00
Salut,

\frac{x-1}{2x +5} = - \frac{3x + 2 }{x - 1} \\ \frac{x-1}{2x +5} + \frac{3x + 2 }{x - 1} = 0\\
 \frac{(x-1)(x-1)}{(2x+5)(x-1)}  +  \frac{(3x+2)(2x+5)}{(x-1)(2x+5)} = 0\\
 \frac{(x-1)^{2} + (3x+2)(2x+5) }{(x-1)(2x+5)} = 0 \\
 \frac{ x^{2}  - 2x + 1 + 6 x^{2}  + 15x + 4x + 10}{(x-1)(2x+5)} =0\\
 \frac{7 x^{2} +17x + 11 }{(x-1)(2x+5)} = 0


2x + 5 ≠ 0
2x ≠ -5
x ≠ -5/2
x -1 ≠0
x ≠1
7x² + 17x + 11 = 0
Δ = b² - 4ac
Δ = 289 - 308
Δ < 0, il n'y a donc pas de solutions à cette équation.

Bonne soirée !